Music Education as a Key Factor in the Full Development of a Child - Kłysz-Sokalska, Natalia (Studia Edukacyjne, 2020)
Music education is a field of pedagogy dedicated to the development of the individual through artistic action, which is manifested in various forms and activities. Properly conducted music education has a beneficial effect on the right development of child. Research shows that music education stimulates the competence of child's language and mathematical skills, affect the development of creative child's personality and its socialization. Neurodidactics points to the significance of playing the instruments to neurogenesis and the development of skills of concentration, memory and attention. Movement to music, however, is developing spatial and mobility coordination, involves sight and hearing, which has a beneficial effect on the mastery of the whole body – muscles and nervous system. Unfortunately, despite the enormity of the positive aspects, music education is treated superficially, which shows a small amount of hours music lessons at school and inadequate preparation and attitude of teachers for music education. The difficulty with which collides every day music education is also a contemporary musical culture. The low level of the presented music content being the only "marketing product" makes that music education becoming too elitist activity, or is forced to follow along with system.